Simulação computacional de um processo de soldagem em operação de um tubo de aço api 5l x70 através do método de elementos finitos - Oliveira, Lucas Silva de (Universidade Federal Rural do Semi-Árido, 2020)
In-service welding is a technique which welding of equipment, pipes and ducts that contain any product or its residues, pressurized or not, with or without flow, is made without the need for operational stops. This is one of the techniques most commonly used in the modification, repair or expansion of a duct network, since it allows intervention without interrupting the flow of the fluid of interest. Due to its peculiarity, such a process requires greater attention in its analysis and execution. In the present work, a computational analysis of this process was carried out in an API 5L X70 steel tube with internal water flow in order to obtain the temperature distribution and the identification of the molten zone and the heat affected zone along the tube. The welding conditions of the proposed model were based on experimental data available in the literature. Computer modeling and simulation was performed using the ANSYS® Workbench 18.0 software, which uses the finite element method. In this, it was necessary to install the moving heat flux extension to simulate the movement of the heat flow. For a better approximation with the physical conditions, the properties of the material (specific heat, thermal conductivity and density) as a function of temperature were sought in the literature, which led to a transient analysis. Heat losses by natural convection (outside the tube), forced convection (inside the tube) and radiation were considered. To obtain the temperature field, virtual thermocouples located in strategic positions were used. We tried to validate the computational model through the experimental data on which it was based. However, despite the good convergence, a study of error analysis is necessary to affirm such validation.
Keywords: Soldagem em operação; Aço API 5L X70; simulação computacional; campo de temperatura; ENGENHARIAS::ENGENHARIA MECANICA